Perilaku Self-Harm pada Remaja Awal di Wilayah Pertanian Kabupaten Jember - Adela Qiyas Aulawi; Yeni Fitria; Enggal Hadi Kurniyawan; Erti Ikhtiarini Dewi; Fitrio Deviantony (KHD Production, 2024)
Early adolescents who are unable to deal with stress well will trigger maladaptive coping mechanisms such as self-harm. Self-harm behavior has become an adolescent trend that can endanger lives. This research aims to explore self-harm behavior among early adolescents at the Agricultural Area in Jember. The method used is quantitative descriptive with a cross-sectional approach. The research sample was obtained using a proportional stratified random sampling technique with a total sample of 376 respondents. Data was collected using the Deliberate Self-Harm Inventory (DSHI) questionnaire and data analysis using univariate analysis. The research results showed that almost all the respondents carried out self-harm in the low category; namely, 319 respondents (84.8%) and the remaining 27 respondents (7.2%) carried out self-harm in the medium category, two respondents (0.5%) did self-harm in the high category, 28 respondents (7.4%) never did self-harm. The low category of self-harm behavior that early adolescents often carry out is deliberately preventing wounds from healing, and the least common is intentionally breaking bones. Early adolescents who engage in low levels of self-harm behavior do not mean that these early adolescents will not attempt suicide. Psychiatric nurses and community nurses are expected to be able to coordinate with schools to develop appropriate nursing interventions for early adolescents who engage in self-harm behavior.